Exeter Universal cemented femoral component: a 20-year follow-up study from a district general hospital. (3rd October 2020) - Khatun, Fouzia; Gill, Damien F.; Atrey, Amit; Porteous, Matthew
Abstract : Aims: We present the results, in terms of survival, clinical outcome, and radiological appearance at 20 years, in a cohort of 225 cemented Exeter Universal femoral components (Stryker, Newbury, UK) implanted in 207 patients, at a district general hospital. Methods: All patients in this study had a total hip arthroplasty (THA) using an Exeter Universal femoral component with a cemented (n = 215) or cementless (n = 10) acetabular component. Clinical and radiological data were collected prospectively at one year, five years, and every five years thereafter. Patients lost to radiological and clinical follow-up (five) were cross-referenced with National Joint Registry (NJR) data and general practitioner (GP) records to assess whether they had undergone revision for any reason. Results: During this period of study 144 patients (157 hips) died (69.78%). Two patients were lost to follow-up, leaving 61 patients (66 hips) available for review (29.33%). Of the 225 hips, three underwent revision for femoral failure with osteolysis. One underwent femoral component revision for treatment of a periprosthetic fracture. Eight underwent revision of the acetabular component only for loosening. Two hips had both components revised, when components were found to be loose at time of revision for acetabular loosening, though no radiological femoral osteolysis. Two patients underwent revision for infection. Using femoral loosening as an endpoint, the survival of the Exeter Universal femoral component was 98.7% (n = 220, 95% confidence interval (CI) 96.1% to 100%) at 20 to 22 years. Survival with an endpoint of revision for any reason was 92.6% (n = 209, 95% CI 89.4 to 95.55), with a 'worst-case scenario' (considering two patients lost to follow-up to have failed), the overall survival rate was 91.7% (n = 207, 95% CI 87.8 to 95.9) at 20 to 22 years. Conclusion: Our results confirm excellent long-term results for the cemented Exeter Universal femoral componentimplanted outside of the originating centre. Cite this article: Bone Joint J 2020;102-B(10):1319–1323.